Efectividad de una intervención integral sobre los factores de riesgo y parámetros clínicos en adultos hipertensos, Santa Rosa - El Oro, 2016. - Aguilar Zambrano, Rosa Marina (2017)
Hypertension (AH) is considered a risk factor for higher lethality diseases which affect the individual and the world population, It is a common clinic in primary health care that leads to a high risk of cardiovascular complications, some studies emphasize that hypertension is favored by educational interventions at level of primary care, the objective is to evaluate the effect of intervention of risk factors and clinical parameters in hypertensive individuals aged 45 to 64 years, Santa Rosa, 2016. A quantitative study with pure experimental design with pretest, posttest and control group was carried out in hypertensive patients aged 45 to 64 years, in the Center of Health Nested Santa Teresita (CNST), during the year 2016.The universe consisted of all hypertensive patients of the CNST; Sample selected in a non-probabilistic way by intention in such a way that there was equivalence in both groups. There were 100 participants, of whom 50 for the intervention group (GI) and 50 of the control group (GC), validated pre-test surveys were used for data collection, later the information was entered for analysis in Epidat version 3.1 It was observed that modifiable risk factors and clinical parameters decreased significantly. It was concluded that educational intercession was effective in all modifiable risk factors and clinical parameters except in the consumption of alcohol and cholesterol respectively. Key words: hypertension, modifiable risk factors.